2018
DOI: 10.1002/14651858.cd012906
|View full text |Cite
|
Sign up to set email alerts
|

Metformin monotherapy for adults with type 2 diabetes mellitus

Abstract: This is a protocol for a Cochrane Review (Intervention). The objectives are as follows: To assess the effects of metformin monotherapy in adults with type 2 diabetes mellitus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 66 publications
0
8
0
Order By: Relevance
“…Recent meta-analyses of randomized controlled trials with metformin mostly concluded an absence of evidence or a neutral effect regarding beneficial effects of metformin on cardiovascular outcomes ( Table 2 ) [ 57 , 58 , 59 , 60 ]. However, the available evidence is weak because most studies were poorly conducted [ 60 ]. With regard to beneficial cardiovascular effects of metformin, we will discuss three trials that are often quoted.…”
Section: Cardiovascular Effectsmentioning
confidence: 99%
“…Recent meta-analyses of randomized controlled trials with metformin mostly concluded an absence of evidence or a neutral effect regarding beneficial effects of metformin on cardiovascular outcomes ( Table 2 ) [ 57 , 58 , 59 , 60 ]. However, the available evidence is weak because most studies were poorly conducted [ 60 ]. With regard to beneficial cardiovascular effects of metformin, we will discuss three trials that are often quoted.…”
Section: Cardiovascular Effectsmentioning
confidence: 99%
“…In a study of 167,254 (46% women) patients with T2DM who were already using MTF and started newer anti-diabetic medications, the incidence of cardiovascular events, after a median observation time of 4.5 years, in women was lower compared to that of men (14.7 versus 16.7 per 1000-person-year) [ 73 ]. Nevertheless, a systematic review of MTF’s overall actions has not been conclusive regarding micro- and macrovascular complications in patients with T2DM [ 74 ].…”
Section: Sex/gender Differences Using Mtfmentioning
confidence: 99%
“…34 Metformin does not cause hypoglycemia or AKI, and the risk of lactic acidosis is exceptionally low. 35 In contrast, withdrawal of metformin in the perioperative period may lead to hyperglycemia. In the absence of contraindications, it would seem reasonable to continue metformin during the perioperative period, including on the day of surgery, aligning with guideline recommendations internationally.…”
Section: Preoperative Metformin Managementmentioning
confidence: 99%